Methodology of Scientific Knowledge of Educational Axiology of Europeanisation - RIDEI, NATALIIA; TYTOVA, NATALIIA; KANOVA, LIUDMYLA; SYDORENKO, TETIANA; ROMANENKO, NATALIIA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2023)
The concrete scientific methodology of sociological research expresses the system of prevailing ruling principles of theoretical concepts, techniques, methods and means of technical regulation, which unites the complex of theoretical and methodological basis and the architecture of the outline of the sociological field of sciences and knowledge, normalized by means of regulators of the system analysis in the quality of sociological research by levels: high – fundamental and philosophical foundations of sociological knowledge; sufficient – approaches, principles, techniques, methods of general scientific interdisciplinary and fundamental knowledge; concretely determinative – set of parametric evaluation in the methods and procedures of the social and philosophical technique of theoretical and applied research. The most used philosophical methods are analysis and synthesis, induction and deduction, abstraction, generalization and specification, observation and analogy, modeling and forecasting. In the perspective of social and philosophical study, the above-mentioned methods of analysis acquire semantic application in the study of social and cultural objects of the organization in the field of education, science and innovation (namely, multidimensional analysis acquires the status of content analysis).